(untitled) (Research, Society and Development, 2025)
Introduction: The demand for emergency care for the elderly has grown gradually, and the role of physiotherapists in Emergency and Urgent Care units was officially recognized in 2018. The objective was to analyze the clinical and epidemiological profile of cardiology patients and the role of physiotherapy in elderly patients admitted to the emergency room of a University Hospital in 2023. Methodology: This is an observational, retrospective, cross-sectional, quantitative study. The study population was selected by electronic search of patients aged 60 years or older, hospitalized for a cardiological cause. Results: The mean age of patients was 72.8 years, with a mean length of hospital stay of approximately 7.73 days. Most patients, regardless of gender, were discharged. The high number of physiotherapy procedures for ventilatory control, ventilatory management, aspiration procedures, and NIV stands out, indicating a high demand for respiratory physiotherapy. For patients receiving invasive mechanical ventilation, there was a high mortality rate of 68.18%. Most patients, representing approximately 87.73% of the total, were transferred to the ICU after admission in the emergency room, while 8.97% were transferred to the ward. Conclusion: The mean age was 72.8 years, with a predominance of males and diagnoses of STEMI, decompensated HF, and NSTEMI. Among the comorbidities, systemic arterial hypertension was the most prevalent. The most frequently used procedures were ventilatory control and management, suctioning, and bed positioning.